2023
DOI: 10.1021/acs.jmedchem.3c01660
|View full text |Cite
|
Sign up to set email alerts
|

New Genetically Engineered Derivatives of Antibacterial Darobactins Underpin Their Potential for Antibiotic Development

Carsten E. Seyfert,
Alison V. Müller,
Danica J. Walsh
et al.

Abstract: Biosynthetic engineering of bicyclic darobactins, selectively sealing the lateral gate of the outer membrane protein BamA, leads to active analogues, which are up to 128-fold more potent against Gram-negative pathogens compared to native counterparts. Because of their excellent antibacterial activity, darobactins represent one of the most promising new antibiotic classes of the past decades. Here, we present a series of structure-driven biosynthetic modifications of our current frontrunner, darobactin 22 ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The darobactins were shown to bind to an open form of the BamA lateral gate by mimicking a β-strand which was at an earlier assembly stage compared to MRL-494 ( 34 ) and the tethered murepavadin and colistin derivative . Mutasynthetic work has led to the identification of more active analogs such as darobactin B ( 36 ) and D9 ( 37 ). Recent total syntheses of darobactin A ( 35 ) have also laid the groundwork for access to new analogs. Finally, a computational approach that searched for genes related to the darobactin operon, facilitated the identification of another new BamA inhibitor, dynobactin ( 38 ), from Photorhabdus australis …”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 99%
“…The darobactins were shown to bind to an open form of the BamA lateral gate by mimicking a β-strand which was at an earlier assembly stage compared to MRL-494 ( 34 ) and the tethered murepavadin and colistin derivative . Mutasynthetic work has led to the identification of more active analogs such as darobactin B ( 36 ) and D9 ( 37 ). Recent total syntheses of darobactin A ( 35 ) have also laid the groundwork for access to new analogs. Finally, a computational approach that searched for genes related to the darobactin operon, facilitated the identification of another new BamA inhibitor, dynobactin ( 38 ), from Photorhabdus australis …”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 99%
“…50,51 Manipulating the darobactin gene cluster and expressing it heterologously resulted in the production of various darobactin analogues. [31][32][33]52 Groß et al substituted F7 → W (D9) and observed a 2−4 times more potent activity compared to DA. 31 Encouraged by the potency of D9, the same research group explored substituting the other amino acids while maintaining F7 → W. Following this, Seyfert et al biosynthetically produced D22, which bears structural resemblance to DB but includes an additional substitution of F7 → W. 33 The antibacterial activity of D22/DB9 is two to four times more potent than D9 against multidrug-resistant Acinetobacter strains, and it exhibits two-fold better activity than DB against various P. aeruginosa isolates.…”
Section: Biological Activity Of Various Darobactinsmentioning
confidence: 99%
“…50 Subsequent biosynthetic modifications led to the discovery of D69, which exhibited activity similar to that of D22. 32 Notably, DA exhibited promising efficacy in murine infection models against both drug-sensitive and drug-resistant Gram-negative bacteria including P. aeruginosa, K. pneumoniae and E. coli with no observed toxicity. 29 The elimination half-life of DA was reported to be 1 h in mice models, and darobactins exhibit good plasma stability.…”
Section: Biological Activity Of Various Darobactinsmentioning
confidence: 99%
“…Most of the reported variants, however, involve substitution of the nonmodified residues of the DarA core region (i.e., positions 2, 4, 6, 7), which collectively showed minimal impact on forming fused bicyclic products. 38,41,44,49,50 In contrast, less is known about enzymatic tolerance to core positions that are modified (i.e., positions 1, 3, and 5). DarE can tolerate substitution of Lys5 with either Arg or Ala to produce darobactins D and 15, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many naturally occurring and engineered darobactin variants have been characterized, which have begun to define the substrate tolerance of DarE. Most of the reported variants, however, involve substitution of the nonmodified residues of the DarA core region (i.e., positions 2, 4, 6, 7), which collectively showed minimal impact on forming fused bicyclic products. ,,,, In contrast, less is known about enzymatic tolerance to core positions that are modified (i.e., positions 1, 3, and 5). DarE can tolerate substitution of Lys5 with either Arg or Ala to produce darobactins D and 15, respectively. ,, Until recently, no experimental data were available regarding the impact of substitutions on DarA core positions 1 and 3.…”
Section: Introductionmentioning
confidence: 99%